Widefield two laser interferometry - Patel, Rikesh; Achamfuo-Yeboah, Samuel; Light, Roger A.; Clark, Matt (Optical Society of America, 2014)
A novel system has been developed that can capture the wide- field interference pattern generated by interfering two independent and incoherent laser sources. The interferograms are captured using a custom CMOS modulated light camera (MLC) which is capable of demodulating light in the megahertz region. Two stabilised HeNe lasers were constructed in order to keep the optical frequency difference (beat frequency) between the beams within the operational range of the camera.